Innovative exergy indicators for analyzing an nZEB building to promote new areas of improvement - Rey-Hernández, Javier M.; Rey-Martínez, Francisco J.; Sala-Lizarraga, Jose M.; Picallo-Perez, Ana (ELSEVIER, 2024)
This study evaluates the energy and exergy performance of buildings towards achieving nearly Zero Energy Building (nZEB) standards by introducing three exergy-based indicators alongside conventional energy metrics. Focused on the LEED Platinum-certified LUCIA building at Valladolid University (Spain), the analysis examines energy and exergy transformations throughout the building’s lifecycle, emphasizing resource consumption, generation systems, and environmental equilibrium across seasons. The study reveals a Non-Renewable Primary Energy Ratio of 67 kWh/m2, closely mirrored by an exergy ratio of 67.2 kWh/m2 due to the high-quality factor of fuel resources. Conversely, the Renewable Primary Energy Ratio stands at 121 kWh/m2, with a corresponding exergy ratio of 88.36 kWh/m2, reflecting the significant contribution of geothermal energy while highlighting areas for demand side optimization. For the same reason, the Renewable Energy Ratio is 0.66 and the Exergy Ratio is 0.56. Despite meeting nZEB criteria, exergy indicators underscore untapped energy-saving potential by aligning resource qualities with demand characteristics. Identifying system weaknesses informs future improvement strategies, potentially enhancing LEED scores. The study advocates for incorporating exergy-based indicators alongside traditional energy metrics in European regulations to accurately assess building performance and define low-ex buildings. Overall, the exergy analysis reveals equipment-specific losses and underscores the qualitative match between energy demand and supply.
Keywords: Construcción; Termodinámica; Exergy analysis; nZEB; Exergy methodology; Exergy indicators; Renewable energy